2013
DOI: 10.5120/12360-8675
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Logic in Sports: A Review and an Illustrative Case Study in the Field of Strength Training

Abstract: As a special form of probabilistic reasoning, the fuzzy logic concept allows the effective realization of approximate, vague, uncertain, dynamic, continuous and, at the same time, more realistic conditions, which are closer to the actual physical world and human thinking. This many-valued idea involves the definition of fuzzy sets and rules as well membership functions. These techniques allow the mapping of classes of objects not only -according to the binary logicto false (0) and true (1) but also to intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…On the other hand, the authors in [44] showed the potential of artificial intelligence techniques in sports using the example of weight training. The same authors also proposed the fuzzy logic approach for the evaluation of strength training exercises [45]. Skiba [53] presented a system and method for computing athletic performance.…”
Section: Application Referencementioning
confidence: 99%
“…On the other hand, the authors in [44] showed the potential of artificial intelligence techniques in sports using the example of weight training. The same authors also proposed the fuzzy logic approach for the evaluation of strength training exercises [45]. Skiba [53] presented a system and method for computing athletic performance.…”
Section: Application Referencementioning
confidence: 99%
“…They also considered that there is a lack of application of fuzzy logic control systems in the fields of sport and training [4].…”
Section: Introductionmentioning
confidence: 99%
“…A controller with the ability to auto-adapt itself to the changes in the surrounding environment must have adjustable parameters and a mechanism for adjusting these parameters [4].…”
Section: Introductionmentioning
confidence: 99%
“…Fuzzy logic has been increasingly used in different fields such as economics [ 13 ], image processing, power engineering, systems engineering, optimization, industrial automation, and robotics with a variety purposes [ 14 ]. Some of the studies in sports are as follows: Novatchkov and Baca [ 15 ] designed a fuzzy logic model for the assessment of strength training exercises in sports. Martínez et al [ 16 ] proposed a fuzzy logic approach for measuring perceived quality in terms of sport and fitness services.…”
Section: Introductionmentioning
confidence: 99%